Activating Students to Speak English through Interpreting Graphs - Khaerati Khaerati; Bungatang Bungatang; Khaidarsyah Khaidarsyah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research is qualitative descriptive research which aimed at finding out (1) whether students actively engage in speaking English through interpreting graphs and (2) whether students have a positive attitude towards the use of graphs in speaking classes. The population of this study consists of first-semester students in the Economics Education study Program at Universitas Patompo for the academic year 2022/2023. The researcher employed purposive sampling technique, involving 30 students. Two types of instruments were used in this research: observation techniques and questionnaires. Observation was used to assess students’ participation in speaking English, while questionnaires were used to find out students' attitudes towards the use of graphs in speaking classes. Data analysis results indicated that 1) the use of graphs in speaking can activate students to speak English. In the interpretation of pie charts, the average speaking frequency of students is 3.3% and categorized into active. In the interpretation of line graphs, the average speaking frequency of students is 3.3% over 90 minutes and categorized into active. In the interpretation of bar graphs, the average students’ speaking frequency was 3.83% in 90 minutes and categorized as very active. 2) The questionnaire indicated that 11 (36.67%) out of 30 students strongly agree, 17 (56.67%) students agree, 2 (6.66%) students rather agree, with none of them disagree and strongly disagree with the use of graphs in speaking class. While the mean score was 57.06, indicating that students have a positive attitude towards the use of graphs in speaking classes.